Towards Cosmopolitanism in German Academia? Shedding Light on Colonial Underpinnings of Communication Research in a Globalized World (Global Media Journal - German Edition, 2021)
Coloniality is a notion that has been key in many disciplines for addressing power relations and their embeddedness in continuous colonial hierarchies. This essay contributes to the reflections on the notion of cosmopolitanism in German academia, focusing on Communication Studies as a starting point. The possibility to develop research at a university in the Global North is usually presented by the hosting countries as a door to productive exchanges among colleagues from different backgrounds. Nevertheless, many hierarchies and pre-established concepts on knowledge production produce forms of epistemic silencing and other forms of violence and limits in these exchanges. The present essay proposes a process of dialogue with decolonial theories to trace roots on the meaning of cosmopolitanism, its borders and possibilities.
Keywords: cosmopolitanism; decolonial theories; communication studies; epistemic violence; universities; internationalization; knowledge production; Germany